2006
DOI: 10.1002/ejlt.200500312
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of fish oil with n‐ octenylsuccinate‐derivatised starch: Flow properties and oxidative stability

Abstract: Microencapsulation of fish oil with n-octenylsuccinate-derivatised starch: Flow properties and oxidative stabilityFish oil with 33% long-chain polyunsaturated fatty acids was microencapsulated in a matrix of n-octenylsuccinate-derivatised starch and glucose syrup and stored at varying temperatures (5, 20 and 40 7C) and relative humidities (11, 33, 48-59 and 75%). Development of lipid oxidation parameters upon storage depended to a certain extent on temperature, but to a much greater extent on relative humidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 33 publications
1
43
1
2
Order By: Relevance
“…The surface oil content of FD and SD samples was relatively high resulting in a high propanal content. A number of studies have been reported on the oxidative stability of microencapsulated fish oil obtained either by SD or by FD, and the results were inconsistent [30,31]. These inconsistent results may be due to changes in conditions of storage and different analytical methods.…”
Section: Stabilitymentioning
confidence: 99%
“…The surface oil content of FD and SD samples was relatively high resulting in a high propanal content. A number of studies have been reported on the oxidative stability of microencapsulated fish oil obtained either by SD or by FD, and the results were inconsistent [30,31]. These inconsistent results may be due to changes in conditions of storage and different analytical methods.…”
Section: Stabilitymentioning
confidence: 99%
“…Use of flavor-masking compounds, in addition to the benefits obtained with entrapment technologies, is also viable in improving consumer acceptance. With the aims of achieving more effective entrapment and driving down DHA/EPA cost per serving, optimized entrapment technology is currently undergoing substantial research efforts throughout multiple industries [17][18][19][20][21][22][23].…”
Section: Materials Of Interestmentioning
confidence: 99%
“…Since it is a solid at room temperature it presents an interesting model compound for studies directed at the entrapment of nano-particulates. Prior commercial successes such as plant sterols in orange juice provide additional incentives and confidence that the probability of a successful wide-scale implementation into human-quality foods is high, and will thus lead to an expanding market [11,[17][18][19][20][21][22][23]]. …”
Section: Materials Of Interestmentioning
confidence: 99%
See 2 more Smart Citations